2006
DOI: 10.2169/internalmedicine.45.1634
|View full text |Cite
|
Sign up to set email alerts
|

Sinus of Valsalva Thrombosis Causing Renal Infarction

Abstract: A 72-year-old man was admitted to our hospital with a renal infarction. On admission, computed tomography (CT)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
(3 reference statements)
0
3
0
1
Order By: Relevance
“…or arterial thromboembolism in the lower legs, as well as ischemic stroke. [26][27][28][29] Even though there were only 3 cases of silent embolic stroke detected on brain MRI in these studies, sinus of Valsalva thrombosis in post-TAVR patients also have potential for coronary arterial occlusion and cerebral or peripheral arterial embolization. As such, assessing potential sinus of Valsalva thrombosis should be an essential component of post-TAVR CT scans.…”
Section: Supplementary Materials Supplementary Tablementioning
confidence: 98%
“…or arterial thromboembolism in the lower legs, as well as ischemic stroke. [26][27][28][29] Even though there were only 3 cases of silent embolic stroke detected on brain MRI in these studies, sinus of Valsalva thrombosis in post-TAVR patients also have potential for coronary arterial occlusion and cerebral or peripheral arterial embolization. As such, assessing potential sinus of Valsalva thrombosis should be an essential component of post-TAVR CT scans.…”
Section: Supplementary Materials Supplementary Tablementioning
confidence: 98%
“…Embolic events associated with unruptured sinus of Valsalva aneurysms are extremely rare. 11 A review of the literature revealed six cases of unruptured sinus of Valsalva aneurysms presenting with embolization (four cases with cerebral embolism, one with peripheral arterial emboli, 7 and one with renal infarction 6 ). We found no reports of embolism in patients with ruptured sinus of Valsalva aneurysms before surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Sinus of Valsalva's aneurysms has been reported as the presumed source of embolism in only six cases. 2 3 4 5 6 7 Herein, we report a patient with the rupture of the right sinus of Valsalva into the right atrium and concurrent pulmonary thromboembolism.…”
Section: Introductionmentioning
confidence: 96%
“…Fuster V. et al (2002) предположили, что тромбоз синуса Вальсальвы при стабильных неэрозированных бляшках аорты может зависеть от гипертромбогенного состояния крови, обусловленного повышенным уровнем липопротеинов низкой плотности, табакокурением, гипергликемией и рядом других условий, связанных с увеличением тромбогенного потенциала крови [9]. В работе Nakata et al (2006) описано утолщение створок аортального клапана с небольшим градиентом давления. Эти изменения могут вызвать турбулентный поток в синусе Вальсальвы, что приводит к повреждению эндотелия стенки аорты.…”
Section: Discussionunclassified